Ferritin and procalcitonin serve as discriminative inflammatory biomarkers and can predict the prognosis of severe fever with thrombocytopenia syndrome in its early stages - Chen, Keping; Sun, Huidi; Geng, Yu; Yang, Chuankun; Shan, Chun; Chen, Yuxin (Frontiers in Microbiology, 2023)
Introduction: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease with high mortality. The pathophysiology of SFTS remains unclear. Hence, the identification of inflammatory biomarkers for SFTS is crucial for the timely management and prevention of disease severity. Methods: A total of 256 patients with SFTS were divided into a survivor group and a non-survivor group. Classical inflammatory biomarkers such as ferritin, procalcitonin (PCT), C-reactive protein (CRP), and white blood cells were investigated for their association with viral load and the clinical significance for predicting the mortality of patients with SFTS. Results: Serum ferritin and PCT showed a positive association with viral load. Ferritin and PCT levels in non-survivors were significantly higher than those in survivors at 7–9 days from symptom onset. The area under the receiver operating characteristic curve (AUC) values of ferritin and PCT for predicting the fatal outcome of SFTS were 0.9057 and 0.8058, respectively. However, the CRP levels and WBC counts exhibited a weak association with viral load. The AUC value of CRP for predicting mortality was more than 0.7 at 13–15 days from symptom onset. Discussion: Ferritin and PCT levels, especially ferritin, could be potential inflammatory biomarkers for predicting the prognosis of patients with SFTS in its early stages.